Effects of audio and visual distraction on patients’ vital signs and tolerance during esophagogastroduodenoscopy: a randomized controlled trial - Sogabe, Masahiro; Okahisa, Toshiya; Fukuya, Akira; Kagemoto, Kaizo; Okada, Yasuyuki; Adachi, Yuka; Kurihara, Takeshi; Nii, Toru; Teramae, Satoshi; Tanaka, Hironori; Tomonari, Tetsu; Okamoto, Koichi; et al. (BMC gastroenterology, 2020)
Esophagogastroduodenoscopy (EGD) provides an indispensable and unambiguous inspection allowing the discovery upper gastrointestinal lesions. However, many patients are anxious about undergoing EGD. Few studies have investigated the influence on patients' vital signs and tolerance during EGD using subjective and objective assessments. This study was a prospective randomized controlled study that investigated the influence of audio and visual distraction on EGD. We randomly divided 289 subjects who underwent EGD into 4 groups (control group, audio group, visual group, combination group) and examined their vital signs, heart rate variability (HRV), psychological items, and acceptance of distraction. Pulse rate (PR) at post-distraction and post-EGD in the 3 distraction groups were significantly lower than those of control group (p <  0.001 and p <  0.01, respectively). Blood pressure (BP) during and post-EGD was significantly higher than that at pre-EGD in control group (p <  0.05), but no significant elevation of BP was observed during the latter half of EGD and post-EGD in the 3 distraction groups. BP at post-distraction improved significantly compared to pre-distraction in the 3 distraction groups (p <  0.05). There was a significant difference in the low-frequency (LF) power/ high-frequency (HF) power at post-distraction and post-EGD among the 4 groups (p <  0.001 and p <  0.001, respectively). The LF power/HF power at post-distraction and post-EGD in the 3 distraction groups was significantly lower than that in control group (p <  0.05). Several items of profile of mood states (POMS) and the impression of EGD at post-distraction improved significantly compared to those at pre-distraction among the 3 distraction groups (p <  0.05). Visual analog scale (VAS) of willingness for the next use of distraction in the 3 distraction groups was excellent because VAS was more than 70. Distractions effectively improved psychological factors, vital signs and some of HRV at pre and post-EGD. Distractions may suppress BP elevation during the latter half of EGD and lead to stability of HRV on EGD. This prospective trial was registered in the University Hospital Medical Information Network (UMIN) Clinical Trials Registry as UMIN000029637. Registered on 20 October 2017.